(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article studies the attraction of local and foreign investments in Surkhandarya region through the use of cross-border tourism potential. Statistical analysis, regional comparison, SWOT and PEST analysis methods, as well as regression-extrapolation and multiplier effect models were used in the research process. Based on the results, it is shown that the development of cross-border tourism in Surkhandarya region has the potential to increase investment activity, expand employment, and ensure sustainable regional development. It is projected that by 2027, tourism investments will reach 60 million USD and the tourism sector will constitute 6.8% of the region’s GDP.